DOPPLEROGRAPHY OF UTERO-PLACENTAL AND FETO-PLACENTAL BLOOD CIRCULATION IN THE CASE OF PLACENTAL INSUFFICIENCY - Abdullajev, R.Ya.; Grishenko, O.V.; Bobrytska, V.V. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine")
With the applicationof Colour and Impuls Doppler regimens the main features of utero-placental and fetal-placenta blood circulation of 68 pregnant women with placental insufficienty were examined.The main quaialitive characteristics of the critical disturbance of blood circulation were the appearance of notch on the diastolic part of Doppler spertrum of uterine artery after 20 weeks gestation and reverse blood flow in the spectrum of mid-cerebral artery and umbilical artery.